KESADARAN BERLALU LINTAS MAHASISWA PENDIDIKAN TEKNIK MESIN UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Rabiman Rabiman; Nurcholish Arifin Handoyono (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study aimed to determine:  1) The level of safety riding for students of Mechanical Engineering Education; and 2) The level of eco riding for students of Mechanical Engineering Education. The type of research used is descriptive. The research population was all students of Mechanical Engineering Education at The Faculty of Teacher Training and Education at Universitas Sarjanawiyata Tamansiswa. The sample was taken using the Stratified random sampling technique which found 199 students. The instrument used is a multiple choice test to measure the level of safety riding and the level of eco riding. The data analysis technique uses descriptive statistics. The result results showed that: 1) The level of safety riding for students of Mechanical Engineering Education was categorized very hight with an average value of 24,78; and 2) 1) The level of eco riding for students of Mechanical Engineering Education was categorized very hight with an average value of 6,85.